Quality of Friction Stir Welding on High Density Polyethylene-Polypropylene Polymer - Febri Budi Darsono; Aldias Bahatmaka; M. Hilman Gumelar Syafei; Salsa Bila Azara; Risky Risky Ramadhani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
One solid-state welding technique that shows great potential in joining polymer materials is Friction Stir Welding (FSW), especially for various polymers like HDPE and PP. FSW can join materials with different mechanical and thermal characteristics without melting the material. The parameters used were a tool rotational speed of 1460 rpm, a feed rate of 30 mm/minute, a plunge depth of 3.84, and a tool tilt angle of 0 degrees for triangular, threaded cylindrical, and tapered groove cylindrical tools. To determine the quality of the welding, the methods used are Non-Destructive Testing (NDT) and Destructive Testing (DT). For NDT, the methods used are visual and radiographic testing. For DT, the tests used are tensile testing, bending testing, hardness testing, and macrostructure testing. From the research results, data were obtained, and the interpretation of the radiographic test showed that the FSW joint of the threaded and grooved tool had no defects, indicating that the FSW joint had good quality. This is supported by tensile strengths of 8 MPa and 4.2 MPa. Meanwhile, the triangular FSW tool showed defects from radiographic testing, such as voids or lack of fusion, with a tensile strength of 1.7 MPa. The highest bending strength obtained from the three tools was for the groove tool, with a bending strength of 16.6 MPa, because the increased material distribution during the welding process created a strong, uniform, and homogeneous surface flow. The bending strengths for the triangular and spiral tools were 15.2 MPa and 5.4 MPa, respectively. The hardness values for the three tools (threaded cylindrical, tapered groove cylindrical, and triangular) were 57.6 SHD, 57.7 SHD, and 60.1 SHD, respectively, which is because the heat from the triangular tool was the highest. The results of the visual test, NDT (Radiography test), are consistent with the macrostructure results: there are no defects in the threads and grooves of the FSW tool, while the FSW tool with a triangular shape has defects in the form of voids.The use of FSW for joining polymer materials in this study is in line with Sustainalbe Development Goals (SDGs) number 4 (Quality Education), 7 (Affordable and Clean energy), 8 (Decent Work and Economic Growth), and 9 (Industry, Innovation and Infrastructure)